Conversion surgery for hepatocellular carcinoma after tyrosine kinase inhibitor treatment. Issue 5 (21st April 2022) - Kaneko, Shun; Tsuchiya, Kaoru; Yasui, Yutaka; Tanaka, Yuki; Inada, Kento; Ishido, Shun; Kirino, Sakura; Yamashita, Koji; Hayakawa, Yuka; Nobusawa, Tsubasa; Matsumoto, Hiroaki; Kakegawa, Tatsuya; et al.
Abstract: Background and Aim: Conversion surgery (CS), which aims to cure after systematic therapy, is only scarcely reported in the field of hepatocellular carcinoma (HCC). However, advancements in systemic therapy for HCC are expected to increase the candidates eligible for CS because of the higher response rate. The aim of this study was to clarify the characteristics of patients who underwent CS after tyrosine kinase inhibitor (TKI) therapy. Methods: In all, 364 patients who were treated with first‐line sorafenib (SOR; n = 292) and lenvatinib (LEN; n = 72) from July 2009 to October 2020 were retrospectively enrolled. The endpoint of this analysis was overall survival (OS), and factors associated with CS are revealed. Results: Six patients underwent CS after TKI therapy, and of these four (1.4%) and two (2.7%) patients received SOR and LEN, respectively. At baseline, patients who underwent CS were significantly younger (median 52 [range, 46–83] years of age, P = 0.019), and their etiology included viral hepatitis, especially hepatitis B virus (HBV) ( P = 0.049). Improvements or maintenance of preoperative modified albumin–bilirubin grade from baseline were observed in five (83.3%) patients, and partial radiologic response was observed in four (66.7%) patients. The median OS and 3‐year survival rate of patients treated with CS were "not reached" and 80.0%, respectively. Conclusion: The patients who underwent CS after TKI therapy for HCC experienced long survival, were relatively young, and exhibited radiologic response to TKIs, and their liver function was either maintained or improved. Therefore, CS may lead to a better prognosis in patients with advanced HCC. Abstract : The patients who underwent conversion surgery (CS) after tyrosine kinase inhibitor (TKI) therapy for hepatocellular carcinoma experienced long survival. The patients who underwent CS were relatively young, and exhibited radiological response to TKIs, and their liver function was either maintained or improved.